A ação antioxidante da glutamina no tecido intestinal e pulmonar de ratos submetidos à isquemia e reperfusão mesentérica - Zabot, Gilmara Pandolfo (2014)
Aims: The aim of the present study was to evaluate possible preventative effects of glutamine in an animal model of gut ischemia/reperfusion (I/R). Materials and methods: Twenty male Wistar rats were divided into four experimental groups: (1) control group (Control) rats underwent exploratory laparotomy; (2) control + glutamine group (Control-GLU) rats were subjected to laparotomy and treated intraperitoneally with glutamine 24 and 48 h prior to surgery; (3) ischemia/reperfusion group (I/R) rats were subjected to occlusion of the superior mesenteric artery for 30 min followed by 15 min of reperfusion; and (4) ischemia/reperfusion + glutamine group (G+I/R) rats were treated intraperitoneally with glutamine 24 and 48 h before I/R. Local and systemic injuries were determined by evaluating intestinal and lung segments for oxidative stress using lipid peroxidation and the activity of superoxide dismutase (SOD), interleukin-6 (IL-6) and nuclear factor kappa beta (NF-κB) after mesenteric I/R. Results: The animals from the G+I/R group exhibited reduced levels of lipid peroxidation, IL-6 and NF-KB and increased SOD activity when compared with the group of rats submitted to I/R without GLU. The findings were statistically significant (p < 0.05). Conclusions: These results demonstrate that pretreatment with glutamine prevents mucosal injury and improves gut and lung recovery after I/R injury in rats.